Insights into teachers' perceptions of the benefits of standardized diagnostic procedures (Pedagogical Horizons, 2024)
Evidence-based teaching should directly incorporate data-based feedback into further instructional design, which is why diagnostic skills are an important aspect of professional competence. The definition of professional competence is based on the COACTIV study, according to which teacher competencies include professional knowledge, attitudes, motivational and self-regulatory components. The importance of non-cognitive competencies for teaching development is confirmed in follow-up studies, which is why the present study asks teachers about attitudes, motivation and self-efficacy beliefs after an in-service training on iKMPLUS, which is mandatory in Austria since 2022. The results show that the advantages of standardized diagnostic procedures are described using the vocabulary of professional expression, but personal attitudes are rarely conveyed, whereas this is significantly more the case when describing the disadvantages.
Keywords: educational research, professional competence, attitudes, diagnostic competence, standardized diagnostic procedures